Efeitos da clorfeniramina na aprendizagem, memória e ansiedade de teleósteos submetidos à ablação telencefálica - Navega, Flávia Roberta Faganello (2006)
The teleost telencephalon provides a good opportunity for studying the function of the vertebrate limbic system because it is simple and present homologies to the limbic structure of higher vertebrates, with hippocampus and amygdala. These animals shows only one area of projection to the telencephalon (Ekström et al., 1995), which has been well preserved through evolution (Peitsaro et al., 2003).